ANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF DABIGATRAN ETEXILATE RELATED SUBSTANCE IN PHARMACEUTICAL DOSAGE FORM BY REVERSE‑PHASE – HIGH‑PERFORMANCE LIQUID CHROMATOGRAPHY - Nawale, Rajesh; Pol, Shankar; Puranik, Prashant; Daud, Anwar; Rajkondawar, Vishal (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to develop and validate new, simple, and selective reverse-phase–high-performance liquid chromatography (RP-HPLC) method for the quantitative determination of Dabigatran Etexilate (DE) and its impurities in pharmaceutical dosage form as per the International Conference on Harmonization guidelines. Method: Chromatographic analysis was performed on Princeton SPHER-l00 C18 (250 × 4.6 mm, 5 μm) HPLC column, maintained at 50°C column temperatures, 6°C sample tray temperature, and detection monitored at 225 nm. The mobile phase consisted of acetonitrile:phosphate buffer (pH 2.5) (33:67 V/V). The flow rate was maintained at 1.0 ml/min. Results: The system suitability results indicate good performance of the system. Specificity study indicates that there is no interference of placebo and blank. The percentage relative standard deviation (RSD) of six preparations for known and unknown impurity in the sample solution is found below 10%; hence, the method is precise. The calibration curve for DE (unknown impurity), Impurity A was linear from 0.38 to 4.5 μg/ml (correlation coefficients [r2] for unknown Impurity [DE] and Impurity A are 0.996 and 0.999, respectively). The calibration curve for Impurity B and Impurity E was linear from 0.38 to 9.00 μg/ml (r2 for Impurity B and Impurity E are 0.999 and 0.999, respectively); hence, the method is linear. Accuracy for DE (unknown Impurity), Impurity A, Impurity B, and Impurity E are found within 80%–120%; hence, the method is accurate. The percentage RSD for a standard solution is found below 5% up to 24 h, and percentage impurity change in the sample solution is found below 0.1% up to 18 h; hence, standard solution is stable up to 24 h, and sample solution is stable up to 18 h. Conclusion: The developed method is new, simple, adequate, specific, precise, linear, and accurate for the determination of DE and its impurities in pharmaceutical dosage forms.